2021
DOI: 10.1371/journal.pcbi.1008621
|View full text |Cite
|
Sign up to set email alerts
|

Neural manifold under plasticity in a goal driven learning behaviour

Abstract: Neural activity is often low dimensional and dominated by only a few prominent neural covariation patterns. It has been hypothesised that these covariation patterns could form the building blocks used for fast and flexible motor control. Supporting this idea, recent experiments have shown that monkeys can learn to adapt their neural activity in motor cortex on a timescale of minutes, given that the change lies within the original low-dimensional subspace, also called neural manifold. However, the neural mechan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(86 citation statements)
references
References 50 publications
6
80
0
Order By: Relevance
“…This is compatible with experimental reports showing substantial changes in motor cortical activity between different movements and/or contexts (Miri et al, 2017;Al Borno et al, 2020;Sun et al, 2020), as well as during prolonged brain machine interface training (Oby et al, 2019). Further analyses will be needed to investigate whether these large changes of cortical activity relate to changes in the effective cortical connectivity (Feulner and Clopath, 2021). Finally, our model also postulates that the thalamic neurons involved in shaping cortical dynamics during motif execution are segregated into motif-specific subpopulations.…”
Section: Experimental Predictionssupporting
confidence: 86%
“…This is compatible with experimental reports showing substantial changes in motor cortical activity between different movements and/or contexts (Miri et al, 2017;Al Borno et al, 2020;Sun et al, 2020), as well as during prolonged brain machine interface training (Oby et al, 2019). Further analyses will be needed to investigate whether these large changes of cortical activity relate to changes in the effective cortical connectivity (Feulner and Clopath, 2021). Finally, our model also postulates that the thalamic neurons involved in shaping cortical dynamics during motif execution are segregated into motif-specific subpopulations.…”
Section: Experimental Predictionssupporting
confidence: 86%
“…Neural network modeling has emerged as a powerful tool to emulate the neural functions and to infer their circuit mechanisms, such as sensory processing [42], decision making [43], and motor control [44][45][46]. One of the biggest successes is the application of feedforward neural networks (i.e.…”
Section: Neural Network Modeling Of Sensory-motor Systemsmentioning
confidence: 99%
“…Their results showed that monkeys could readily learn to control the cursor when the change was within the original subspace, whereas they were less able to learn the new mapping if it was outside of the original subspace. To understand the circuit mechanisms that cause the difference in the motor learning ability, Feulner and Clopath (2020) trained RNNs and compared their adaptability to change of the BCI mapping within and outside of the original subspace [45]. Their results showed that RNN can predict error feedback signal more correctly when the change was within the original subspace than when it was outside of the original subspace and resulted in the better learning performance, suggesting that the low-dimensional subspace provided a constraint to correctly estimate the error feedback for motor learning.…”
Section: Rnn Modeling Of Motor Control Preparation and Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…RNNs trained on motor, cognitive and BCI tasks exhibit many striking similarities with the activity of neural populations recorded in animal studies [Mante et al, 2013, Sussillo et al, 2015, Rajan et al, 2016, Song et al, 2017, Wang et al, 2018, Michaels et al, 2020, Perich et al, 2021, suggesting a fundamental similarity between the two. Previous work using RNNs to model the BCI experiment described above [Sadtler et al, 2014] showed that network covariance can be highly preserved even when learning is happening through weight changes within the network [Feulner and Clopath, 2021]. Thus, contrary to widespread intuition, functionally relevant synaptic weight changes may not necessarily lead to measurable changes in statistical interactions across neurons [Das and Fiete, 2020].…”
Section: Introductionmentioning
confidence: 95%